Discussing the Development in the Real Estate Sector in the Framework of University-City Interaction - Mete Korhan Özkök; Büşra Begen Okay (Iconarp International Journal of Architecture and Planning)
Universities exert a considerable influence on urban economies through the direct and indirect consumption they generate within the city. The former is attributable to the expenditure of students and staff, while the latter is a consequence of the demands they create for accommodation, transport, trade, and services. One of the most fundamental areas where these effects can be monitored is the housing and accommodation shaped by the demands of students and staff. Following the establishment of Kırklareli University in 2007, a notable increase in human mobility has been observed in the city center of Kırklareli, accompanied by significant changes in the spatial order. The principal objective of this study is to examine the housing-based spatial transformation and tendency in the city center of Kırklareli in terms of the defined periods following the establishment of the university. In this context, housing sale data and its distribution were analyzed in a spatial/structural dimension using the "Land Registry Transaction Statistics" and "Parcel Query-Analysis-Independent Section Sales Density Distribution database," which were published by the Republic of Turkey Ministry of Environment, Urbanization and Climate Change-General Directorate of Land Registry and Cadaster. The increase and tendency were evaluated. A statistical query and correlation analysis were conducted on the data, with a particular focus on establishing a comparison between the change in population and the number of students, as well as academic and administrative staff. The resulting data were then subjected to a process of interpretation. In addition, current master plans were evaluated, and suggestions were developed for the factors that should be considered in urban planning. The study revealed that, regardless of the current population development, student-oriented dynamics directly affect the real estate sector in terms of housing sales, mobility, and spatial transformation due to the growth of the urban population and the increase in demand.